Study on the Optimal Configuration Strategy of Photovoltaic and Energy Storage in Distribution Network. Issue 4 (May 2019) - Zhu, Jiawei; Jia, Yanbing; Xie, Dong; Luo, Gang
Abstract: Aiming at the scenario of joint optimization of distributed optical storage in distribution network, this paper takes the maximum net profit of optical storage system as the goal. At the same time, this paper considers the high cost of energy storage battery, and combines the load characteristics, the energy storage operation characteristics and China's electricity price policy to construct the optical storage system investment income model. On the basis of satisfying the power balance and the performance constraints of the energy storage battery, an optimization model considering the net profit of the optical storage system is established, and the YALMIP toolbox and CPLEX program are used to solve the problem in MATLAB. Finally, the results of the energy storage configuration are tested in the IEEE-33 node system. The test results prove the effectiveness of the optical storage joint optimization configuration strategy based on the net profit of the optical storage system as a technical indicator.